2019
DOI: 10.1088/1742-6596/1244/1/012016
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Test and Toxicity Test for Methanol Extract of Belajang Susu (Scindapsus pictus Hassk.)

Abstract: Plant Belajang Susu (Scindapsus pictus Hassk.) is a species of the genus Scindapsus including Araceae family that has long been used by Mambi traditional communities as anticancer. Plant that include genus Scindapsus are generally used as ornamental plants, and there are also used as medicinal plants because they contain active compounds and can be antiinflammatory, analgesic, antioxidant and anti-tumor. Methods used included of extraction or maceration, phytochemical test, fractionation and bioactivity test e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…MCF-7 cell line has been used for examining the cytotoxic effect of antimalarial drugs in several previous studies. [27][28][29][30][31][32] Cancer cells are more susceptible to toxic drugs than the majority of normal cells because they actively divide at considerably greater rates, and this is related to mitotic spindles and DNA replication in cancer cells. 25,48 Other study showed relatively uniform toxicity results of cell lines and normal cell lines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MCF-7 cell line has been used for examining the cytotoxic effect of antimalarial drugs in several previous studies. [27][28][29][30][31][32] Cancer cells are more susceptible to toxic drugs than the majority of normal cells because they actively divide at considerably greater rates, and this is related to mitotic spindles and DNA replication in cancer cells. 25,48 Other study showed relatively uniform toxicity results of cell lines and normal cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…26 Other studies have been using breast cancer cell MCF-7 in antimalarial toxicity test. [27][28][29][30][31][32] In addition, cancer cell lines and normal cell lines exhibited relatively uniform toxicity results. 24 So, the purpose of this study is to evaluate the antimalarial effectiveness of fractions 14 and 36K against Plasmodium berghei and their toxicity on MCF-7 cells as a novel prospective antimalarial drug candidate in vitro.…”
Section: Introductionmentioning
confidence: 99%